Radioactive and Stable Ion Beam production at GANIL. Issue 1 (1st April 2022) - Dubois, M.; Bajeat, O.; Barué, C.; Bosquet, V.; Chauveau, P.; Damoy, S.; Frigot, R.; Hormigos, S.; Jardin, P.; Lechartier, N.; Lemagnen, F.; Maunoury, L.; et al.
Abstract: GANIL Facilities deliver ion beams from Proton to Uranium up to 95MeV/A. The Cyclotron facility combined with the SPIRAL1 facility provides Stable Ion Beams (SIB) since 1983 and Radioactive Ion Beams (RIB) since 2001 for Physics experiments. R&D of new stable and radioactive beams are continuously under progress matching physicist requirements. During the last ten years, the SPIRAL1 facility was upgraded to extend its capabilities to deliver RIBs of condensable elements. After a new one delivered in 2019, off-line R&D's have been done on the Target Ions Source System and also on the Charge Breeder to improve efficiencies and achieve an operational and reliable facility. In parallel, the commissioning of the LINAC-SPIRAL2 facility started in 2019 with a proton beam production. In 2020, a 16 kW proton beam was delivered for the first time on the Neutron For Science physics area, and a 4 mA beam of 4 He 2+ was produced with the PhoenixV3 ECR ion source to mimic a deuteron beam. In this article, an overview of GANIL ion sources, beam properties and future developments are described.